Post‐mammographic screening behaviour: A survey investigating what women do after being told they have dense breasts. (10th September 2020) - Darcey, Ellie; Hunt, Emma Jane; Keogh, Louise; McLean, Kirsty; Saunders, Christobel; Thompson, Sandra; Woulfe, Catherine; Wylie, Elizabeth; Stone, Jennifer
Abstract: Issue addressed: Despite widespread calls for women undergoing mammographic screening to be informed of their breast density, concerns remain as to how this is interpreted and acted upon given the absence of evidence‐based supplemental screening recommendations for women with dense breasts. This study investigates the action women take in response to being notified they have dense breasts and what subsequent advice women receive from health professionals. Methods: Via a survey of nearly 7000 women, we assessed the post‐screening actions of women attending a population‐based mammographic screening program (BreastScreen) in Western Australia from 21 November 2017 to 19 April 2018. Women who reported that they were notified they had dense breasts were compared to controls (where applicable). Descriptive and logistic regression analyses were used to summarise responses from 6, 183 women. Results: Half of women notified that they have dense breasts consulted or intended to consult their General Practitioner (GP), particularly those notified for the first time (55%). Of those notified women who consulted their GP, 50% were referred to have supplemental screening. Overall, 20% of women notified as having dense breasts reported that they had an ultrasound due to their breast density. Conclusion: Self‐reported health service usage after mammographic screening is higher in women who have been notified they have dense breasts. So what? There is growing pressure for screening programs in Australia and internationally to routinely measure and report breast density to participants. Results from this study can inform screening programs of the likely impact of breast density notification on health service usage. While more information is needed to fill knowledge gaps in recommended action for women with dense breasts, the greatest risks to women arise from not being screened. Hence, health promotion practitioners and health providers should continue to encourage women to participate in BreastScreen programs.